EFEKTIVITAS PROGRAM KARTU INDONESIA PINTAR (KIP) TAHUN 2021-2022 - Rawinarno, Tjahyo; Alynudin, Suhud; Widiarto, Agus; Setyoko, Haryo; Shafira, Najwa (LPPM STIA Banten, 2024)
Smart Indonesia Card programme almost ten years after president’s instruction. The goal is for insurance Indonesia's student rights to study at school. Hence, through this research hopefully can be the solution of the programme’s problem. The method of this qualitative research is the approach from Cunningham (2016). Reason of declined drop out's number is the minimum of control in Smart Indonesia Card utilisation